The Automatization of a New Thermography Method Using Invasive Nociceptive Stimulation to Confirm an Autonomic Phenomenon within a Trigger Point Referred Pain Zone - Skorupska, Elżbieta (Brain Sci, 2021)
The trigger points (TrPs) related to chronic low back pain that mimic sciatica have been lately recognized and included in the International Classification of Diseases, 11th Revision. This study examined the MATLAB software utility for the objective stratification of low back pain patients using the Minimally Invasive Procedure (MIP). The two diagnostic MIP parameters were: average temperature (ΔTavr) and autonomic referred pain (AURP). Chronic sciatica patients with TrPs (n = 20) and without TrPs (n = 20) were examined using the MIP. A significant increase in both parameters was confirmed for the thigh ROI of the TrP-positive patients, with ΔTavr being the leading parameter (p = 0.016, Exp(β) = 2.603). A continued significance of both parameters was confirmed from 6′00″ to 15′30″ (p < 0.05). The maximum AURP value was confirmed at 13′30″ (p < 0.05) (TrPs(+) 20.4 ± 19.9% vs. TrPs(-) 3.77 ± 9.14%; p = 0.000; CI (0.347,0.348)).